Study of monocomponent gas adsorption capacity of activated carbons obtained from cashew nutshell (2024)
The depletion of the world's oil reserves and the problem of climate change due to the increase in carbon dioxide levels in the atmosphere have led to an increasing search for new alternative sources of clean energy. The ideal fuel to produce energy would be hydrogen since its combustion would produce a large amount of energy while the only biproduct is water. The low density of hydrogen at room temperature means it must be stored at very high pressures, which is not recommended for use in everyday transportation vehicles. One of the alternatives to reduce storage pressure is the use of adsorbent materials. Activated carbon presents advantages over other adsorbent materials since it can be obtained with a large specific surface area, has a low production cost, has fast adsorption/desorption kinetics, and its surface chemistry can be easily modified. The main goal of this study is to prepare microporous materials for hydrogen storage from the agricultural residue known as cashew nut shell and determine the best conditions that allow us to obtain such materials. The cashew nutshell is a residue. As cashew tree plantations are increasing throughout Colombia, this has resulted in a considerable amount of residue. These shells contain an inedible oil that does not degrade easily; in addition, this oil prevents the shell from being used as a source of energy due to the toxic components that are released when burned. Therefore, finding an effective way to use these shells would have a positive benefit for the cashew industry. In the production of activated carbons, different activating agents and activation temperatures are used for each agent. The activated carbons obtained are texturally and chemically characterized and are then subjected to high-pressure hydrogen adsorption tests. The performance for storing hydrogen of these activated carbons is compared with other materials. It was found that the adsorption of hydrogen at high pressures is not only favored by a high surface area and micropore volume but also the ratio of the microporous to the mesoporous. The porous network morphology of each material must also be taken into account, which can facilitate the access of the gas to the micropores, increasing their adsorption capacity. This network morphology was especially developed by directly activating the precursor with potassium carbonate. Additionally, the research explores the performance of the materials obtained in comparison to other gases of interest, such as CH4 and CO2. In both cases, the material that presented the highest uptake was the one that was activated in a single step with potassium carbonate.